Determination of organic pollutants in coking wastewater by dispersive liquid–liquid microextraction/GC/MS. Issue 9 (10th May 2013) - Song, Guoxin; Zhu, Chunyan; Hu, Yaoming; Chen, Jianmin; Cheng, Hefa
<x xml:space="preserve">Abstract</x> A method based on dispersive liquid–liquid microextraction coupled with GC/MS was developed for quantitative analysis of the major organic pollutants listed in the United States Environmental Protection Agency method 8270 and the 15 European‐priority polycyclic aromatic hydrocarbons in coking wastewater. The major parameters such as extraction solvent, dispersive solvent, solution pH, and extraction time were systematically optimized. The optimum extraction conditions were found to be: 15 μL mixture of 2:1 v/v carbon tetrachloride and chlorobenzene as the extraction solvent, 0.75 mL ACN as the dispersive solvent, solution pH of 8, and extraction time of 2 min. For the major pollutants listed in the United States Environmental Protection Agency 8270, the linear ranges were 0.1 to 100 mg/L, the enrichment factors ranged from 452 to 685, and the relative recoveries ranged from 67.5 to 103.5% with RSDs of 4.0–9.1% (n = 5) at the concentrations of 10 mg/L under the optimum extraction conditions. For the 15 polycyclic aromatic hydrocarbons, the linear ranges were 0.1 to 100 μg/L, the enrichment factors ranged from 645 to 723, and the relative recoveries ranged from 94.5 to 107.6% with RSDs of 4.6–9.0% (n = 5) at the concentrations of 10 μg/L. The usefulness of the developed method was demonstrated by applying it in the analysis of real‐world coking wastewater samples.